PTCH1 mutations' role in keratocystic odontogenic tumors and nevoid basal cell carcinoma syndrome - Archana Behera; Mukesh Kumar Dharmalingam Jothinathan (Oral Oncology Reports)
Nevoid basal cell carcinoma syndrome (NBCCS) is a typical autosomal dominant disorder distinguished by malformations in development and an increased susceptibility to cancer. Keratocystic Odontogenic Tumors (KOTs) are highly malignant lesions of the jaw that, in isolation or conjunction with NBCCS, may be associated with PTCH1 (patched 1) mutations. The function of PTCH1 mutations in the pathogenesis of KOTs is the subject of this study, which compares cases associated with NBCCS and spontaneous KOTs. The genetic analyses revealed that PTCH1 mutations were the most prevalent in both KOTs varieties, while Smoothened (SMO) mutations were rare, indicating that they play a negligible role. These mutations increase the activity of the Sonic Hedgehog (SHH) Pathway, indicating that pathway inhibitors may be a viable treatment option. These findings validate the significance of PTCH1 in KOTs aggressiveness and recurrence, supporting the use of genetic testing to improve treatment and diagnosis. This underscores the importance of targeted therapies, specifically in instances of resistance, and the tailoring of treatment plans under genetic knowledge.